EMPLOYMENT 5.0: THE RELATIONSHIP BETWEEN STUDENTS' PERCEPTION OF WELDING TECHNOLOGY COURSES AND THE WORK READINESS - Sapitri Januariyansah; Dwiki Muda Yulanto; Batumahadi Siregar; Hasianna Nopina Situmorang; Safri Gunawan; Rahma Doni (Department of Mechanical Engineering Education, 2025)
Work readiness is an important factor in overcoming the high unemployment rate of college graduates. Various efforts have been made to improve the quality of work readiness, such as through welding technology courses. However, practical contributions measured through statistical analysis have never been made to date. The purpose of this study is to analyze the relationship between students' perceptions of welding technology courses and work readiness. This type of research was ex-post facto research with a quantitative approach. The data collection technique used a questionnaire technique. The data analysis technique used correlational inferential analysis. The results of the study indicate that students' perceptions of welding technology courses (X) have a relationship with work readiness (Y) in the moderate category (r = 0.577) with the amount of contribution based on the coefficient of determination (r2 = 0.333) which means that variable X contributes 33.3% to Y. Based on the regression coefficient (b = 0.228) which shows that if variable X increases by 1 unit then variable Y increases by 0.228. The implications of this study indicate that welding technology courses make a moderate contribution to improving work readiness